Use of a diode Laser in an excisional biopsy of two spoonlikeneoformations on the tongue tip - Tarullo, A.; Laino, L.; Tarullo et al., A. (Acta Biomedica Atenei Parmensis, 2011)
The 810 nm diode laser, due to its high affinity with haemoglobin (elective chromatophore) revealed, by itself, as elective instrument for surgical excision of the tongue, an organ highly vascularized and sensitive to the laser cutting action. The advantages for its use, with respect to the traditional cold blade surgery, are its haemostatic effect (which avoids to close wounds by stitches) and, not less important, the decontaminant effect of the laser ray, due to either the thermal raising created on cutting line and/or the specific selective action exerted on the bacterial membrane by its wavelength. Finally, the analgesic effect of the diode laser contributes to consider this kind of procedure more comfortable for the patient who often roundly requires its use.